Florida Dairy Farm Situation and Outlook 2004 - Russ Giesy; Albert de Vries; Calvin Covington; Richard Kilmer; Dave Bray; Dan Webb (EDIS)
The Dairy Business Analysis Program (DBAP) is a cooperative effort of the Universities of Florida and Georgia, Southeast Milk Inc., and Southeast National Dairy Herd Improvement Association, Inc. (DHIA). This project annually surveys participating dairy farms about their revenues, expenses, and investments. This document is AN147, one of a series of the Department of Animal Sciences, Florida Cooperative Extension Service, UF/IFAS. Published February 2004.